Transformasi Pakaian Masyarakat Batak di Bawah Pengaruh Budaya Kolonial Belanda, 1893–1942: Analisis Foto Koleksi Digital Library Universitas Negeri Medan - Talenta Febriani Situmeang; Desman Poulin Sitohang; Nurul Khoiriyah Siregar; Muhammad Ardiansyah Rasuna; Joshua Jofrat Erikogusto Hutapea; Siti Mawar Naibaho; Pidia Amelia (Medan Resource Center, 2025)
This study examines the transformation of Batak clothing under the influence of Dutch colonial culture between 1893 and 1942, as reflected in historical photographs from the Digital Library of Universitas Negeri Medan. The research is grounded in the socio-cultural dynamics of colonial encounters, where clothing became a visible marker of adaptation, resistance, and negotiation of identity among the Batak people. The central research question explores how Dutch colonial values and modernity shaped local dress patterns and aesthetic expressions during this period. Using a qualitative visual analysis method, the study systematically interprets photographic archives to uncover shifts in material, style, and symbolic meaning of Batak attire. The findings reveal that colonial interaction not only introduced new fabrics and tailoring techniques but also influenced social hierarchies, gender representation, and perceptions of respectability within Batak society. The study concludes that clothing transformation during the colonial era reflects a hybridization process—merging indigenous traditions with colonial modernity—signifying both cultural adaptation and subtle resistance to colonial hegemony.